Victims’ perceptions of the police response as a predictor of victim cooperation in the Netherlands: a prospective analysis - Koster, Nathalie-Sharon N. (Psychology, crime & law, 2017)
The current study prospectively explores whether crime victims’ willingness to cooperate with the police is predicted by victims’ perceptions of police officers’ behaviour with regard to their case through their perceptions of police legitimacy. Structural equation modelling was used to examine the interrelationships between the study variables while controlling for baseline values among a sample of 201 crime victims in the Netherlands. Results indicate that victims’ perceptions of procedural justice and police performance were predictive of both indicators of perceived police legitimacy (i.e. obligation to obey the law and trust in the police). Moreover, victims’ willingness to cooperate with the police was indirectly predicted by victims’ perceptions of procedural justice and police performance, through their perceptions of obligation to obey the law. These findings suggest that police officers may play an important role in stimulating victims’ willingness to cooperate with the police by treating victims fairly and by taking investigative actions to solve the crime.